PENGARUH MOTIVASI INTERNAL DAN MOTIVASI EKSTERNAL TERHADAP KINERJA KARYAWAN PADA PT. ARYO BIMO PONTIANAK - admin, SYARIF ABDUL RIFAL B11110125 (Jurnal Manajemen Update, 2016)
This research aimed to examine whether there is an influence of internal and motivation external on the perfomance of the employees of PT. ARYO BIMO PONTIANAK. This research was designed as a descriptive and casuality study. The population of this research was employees of PT. ARYO BIMO PONTIANAK in the operational division with 71 respondents. Sample withdrawal technique used is the of saturation sampling technique. The analysis technique used was the multiple linear analysis using the SPSS version 20.0. The result of data processing indicated that based on the test using the multiple linear regression model, the internal and external motivation showed a unindirectional relationship (positive) on the perfomance of employees with a coefficient of determination (R2) amounting to 31% while the rest 69% was influenced by other variabels not examined in this research. Partially, it was found that the internal motivation variable had a significant influnence on perfomance. While the external motivation variable partially had no significant influence on the perfomance of the employees. Keywords: internal motivation, external motivation and perfomance